Leveraging applications of formal methods, verification and validation. Applications and case studies 5th International Symposium, ISoLA 2012, Heraklion, Crete, Greece, October 15-18, 2012, Proceedings, Part II - Steffen, Bernhard; Margaria, Tiziana (Lecture Notes in Computer Science, 2012)
The two-volume set LNCS 7609 and 7610 constitutes the thoroughly refereed proceedings of the 5th International Symposium on Leveraging Applications of Formal Methods, Verification and Validation, held in Heraklion, Crete, Greece, in October 2012. The two volumes contain papers presented in the topical sections on adaptable and evolving software for eternal systems, approaches for mastering change, runtime verification: the application perspective, model-based testing and model inference, learning techniques for software verification and validation, LearnLib tutorial: from finite automata to register interface programs, RERS grey-box challenge 2012, Linux driver verification, bioscientific data processing and modeling, process and data integration in the networked healthcare, timing constraints: theory meets practice, formal methods for the developent and certification of X-by-wire control systems, quantitative modelling and analysis, software aspects of robotic systems, process-oriented geoinformation systems and applications, handling heterogeneity in formal development of HW and SW Systems.